Hydroalkylation of terminal aryl alkynes with alkyl diacyl peroxides. Issue 50 (14th December 2016) - Li, Yougui; Ge, Liang; Qian, Bo; Babu, Kaki Raveendra; Bao, Hongli
Graphical abstract: Highlights: Diacyl peroxides as electrophiles for hydroalkylation of aryl alkynes. Z -Selective hydroalkylation of alkynes. Mild reaction condition. Abstract: A photo and nickel co-catalyzed hydroalkylation of terminal aryl alkynes enabled Z -preferred olefin synthesis has been developed under mild conditions. Alkyl diacyl peroxides were utilized as a new type of alkylation reagents and afforded Z -olefins as the major products in moderate to good yields.